Applications of MXene and its modified materials in skin wound repair - Zhang, Ziyan; Qi, Zhiping; Kong, Weijian; Zhang, Renfeng; Yao, Chunli (Frontiers in Bioengineering and Biotechnology, 2023)
The rapid healing and repair of skin wounds has been receiving much clinical attention. Covering the wound with wound dressing to promote wound healing is currently the main treatment for skin wound repair. However, the performance of wound dressing prepared by a single material is limited and cannot meet the requirements of complex conditions for wound healing. MXene is a new two-dimensional material with electrical conductivity, antibacterial and photothermal properties and other physical and biological properties, which has a wide range of applications in the field of biomedicine. Based on the pathophysiological process of wound healing and the properties of ideal wound dressing, this review will introduce the preparation and modification methods of MXene, systematically summarize and review the application status and mechanism of MXene in skin wound healing, and provide guidance for subsequent researchers to further apply MXene in the design of skin wound dressing.